American Studies in Norway: Historic Ideals and Contemporary Challenges - Cassandra Falke (American Studies in Scandinavia)
Because of its particular history of institutionalization, American studies in Norway has come to fill a unique role in higher education, one that requires broader recognition to secure the field a stable future. In this article, Falke connects the past of American studies in Norway to its present by focusing on three founding moments. These three are: the establishment of the Fulbright Program, which she uses to discuss shifts in funding American studies; the creation of the professorship of American studies in Oslo, which clarifies differences in the goals of British and American studies; and the initiation of the Salzburg Seminar, which reveals the field´s interdisciplinary core. The article closes with three generalizations about the landscape of American studies teaching in Norway today related to America as a political imaginary, internationalization within American studies as a discipline, and the presumed relationship between American literature and lived experience of the culture.